Thrombocytopenia & Mean Platelet Volume in Plasmodium Vivax Malaria Cases Presenting at A Tertiary Care Hospital - Salahuddin, haji Khan Khoharo, Abdul Karim Soomro, Abdul Rashid Baloch, Mujahid All Chandio , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the frequency of thrombocytopenia and mean platelet volume (MPV) cases reporting at a tertiary care hospital of S indh Methods: This cross sectional study was performed in the department of Medicine, lira University Hospital, Hyderabad from Feb 2015 to Nov 2016. A sample o 1312 P. vivax eases were studied according to the inclusion and exclusion criteria. Malaria was diagnosed on thick and thin blood smears by light microscopy. Complete blood counting was performed by Sysmex KX-21 hematology analyzer. Hemoglobin, hematocrit, platelets and MPV were counted on this fully automated hematoanalyzer. Data variables were analyzed by statistical software SPSS ( ver 21 .()) at 95°.0 CI ( P < 0.05). Results: Thrombocytopenia was detected in 229 (73.4%) and normothronibocytosis in 83 (26.6" ) (P-0.0001). Of 229 thrombocytopenia cases; the mild, moderate and severe thrombocytopenia were noted in 32 (13.9%), 157 (6g,5%) and 40 (17.4%) respectively. MPV was raised in thrombocytopenia cases as 13.16±1.62 11 compared to 7.87±3.12 fl in normothrombocytosis eases (P=0.0001). Conclusion: The present study observed high frequency of thrombocytopenia and elevated mean platelet volume in Plasmodium vivax malaria.